PENDIDIKAN ANTI KEKERASAN PERSPEKTIF AL-QUR’AN DAN IMPLEMENTASINYA DALAM METODE PENGAJARAN PAI - Muhammad Insan Jauhari (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
The Violence in educationis a behavior that exceed the limit and violate the rules in education.There area variety of cases that occurred against the background of different problems, to cause some negativeeffects for the victims. Schools should have a place for children to get an education and teaching, ratheras a place for children to get violent. The purpose of this obserb was to describe the concept of nonviolence education in the Qur’an and implementation in PAI. Collecting data using the method ofdocumentation. The results showed the first, non violence education in the QS.Ali‘Imran:159 including;gentle, forgiving, democracy and resignation. Second, the implementation in the PAI includes thefunctions and duties of teacher to be thoughtful and open and dialogical stance put forward in thelearning relevant.Keywords: NonViolence Education, Teaching Methods PAI.